Social Impact Analysis of Inclusive Education Policy through the Perspective of Online Community Education - Mesra, Romi; Korompis, Manuel Vidi; Tuerah, Paulus Robert; Salem, Veronike E.T (Laboratorium Program Studi Pendidikan Sosiologi Unima, 2024)
The purpose of this study is to analyze the social impact of inclusive education policies through the perspective of online educational communities. The method used is a systematic literature review with a qualitative approach, analyzing relevant studies from various academic databases. The results show that online communities play a crucial role in raising awareness of inclusive education, changing attitudes towards disabilities, bridging the gap between policy and practice, and facilitating the exchange of knowledge and support among stakeholders. These findings highlight the importance of considering the dynamics of online communities in the development and implementation of inclusive education policies. This study provides valuable insights for policymakers and education practitioners on how to leverage digital platforms to support the transformation towards a more inclusive education system.